The implementation of case formulation by probation officers: service user and carer views - Brown, Susan; Völlm, Birgit (Taylor & Francis, 2016)
Background: The recent UK Government strategy on high-risk offenders with personality disorders (PD) proposes improved identification of this group, assessment of their treatment needs through case formulation (CF) and the subsequent provision of treatment pathways. Little is known about service user and carer views on this strategy.